PENEGAKAN HUKUM TERHADAP PELAKU TINDAK PIDANA PEDOFILIA - Salundik (Sekolah Tinggi Ilmu Hukum Tambun Bungai Palangka Raya, 2016)
Children are the assets of which will determine where the children will be taken, therefore children need to be protected and prepared as early as possible with a wide range of knowledge and good character , so that the human resources quality that is needed to build the nation. One act of sexual violence against children is a pedophile or paedofhilia. Pedophilia is one of several forms of sexual deviation which is also called Paeafilia. People with pedophilia have deviant sexual behavior which showed that children under the age of an object for the gratification of sexual needs. Law enforcement against perpetrators of the criminal acts of pedophilia committed by parties who are obliged to enforce the law and justice, from police, prosecutors and the courts with reference to the provisions of the legislation in force. With the presence of Law Number 35 Year 2014 on the Amendment of Act No. 23 of 2002 on the protection of Children is expected to provide legal certainty for law enforcement against criminal pedophilia. This is needed so that children get legal protection.